Automation of Technical Documentation Validation Workflows Based on GitHub Using n8n During Software Development Stages - Raden D Ahmad H; Endra Abdul Hadi; Enang Rusnandi (Politeknik Mardira Indonesia, 2025)
This research addresses a significant gap in workflow automation literature by investigating the integration of technical documentation validation with developer-centric notification mechanisms. Employing Rapid Application Development methodology coupled with quasi-experimental design, the study developed and validated an end-to-end automation system leveraging n8n, GitHub, and WhatsApp integration for README.md validation. The implementation employed JSON-based workflow scripting to establish automated trigger sequences initiated by repository commits, facilitating real-time validation through content parsing and format verification. Execution testing demonstrated system reliability through iterative debugging and successful notification delivery across multiple test scenarios. The research successfully establishes a practical framework demonstrating the viability of comprehensive documentation automation solutions that extend beyond isolated CI/CD functions, providing immediate, actionable feedback to development teams through preferred communication channels while minimizing implementation complexity.